Based on wearable sensory device in 3D-printed humanoid: a new real-time sign language recognition system - Bilal Zaidan (Tanjung Malim, 2021)
Based on wearable sensory device in 3D-printed humanoid: a new real-time sign language recognition system by Bilal Zaidan